THE ROLE OF WOMEN IN LIVESTOCK DECISION MAKING IN AGRO-PASTORAL SYSTEMS IN KENYA. A CRITICAL LITERATURE REVIEW - Olenje, Stephen (American Journal of Livestock Policy, 2022)
Purpose: Today, women represent half of the world's population and one third of the official labor force, but they receive only one percent of the total global income and own less than one percent of the world property. The primary objective of this research was to establish how changes in socio-economic factors affect the participation of women of different economic and educational statuses in livestock management and marketing, particularly in terms of their labor inputs and allocation of productive resources. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Finding: The concomitant assumption formulated for this objective was that even as women's labor contribution to the household in the livestock industry has increased, there has not been a corresponding increase in their decision-making ability. Unique Contribution to Theory Practice: The study recommends that any efforts aimed at empowering women in livestock decision-making should first of all improve women's status through increased education opportunities and participation in formal employment in order to give them independent incomes.